Simulation of Acute Haemodynamic Outcomes of the Surgical Strategies for the Right Ventricular Failure Treatment in Pediatric LVAD. Issue 12 (December 2015) - Di Molfetta, Arianna; Ferrari, Gianfranco; Iacobelli, Roberta; Filippelli, Sergio; Fresiello, Libera; Gagliardi, Maria G.; Toscano, Alessandro; Trivella, Maria G.; Amodeo, Antonio
Background: Right ventricular failure (RVF) is one of the major complications during LVAD. Apart from drug therapy, the most reliable option is the implantation of RVAD. However, BIVAD have a poor prognosis and increased complications. Experiments have been conducted on alternative approaches, such as the creation of an atrial septal defect (ASD), a cavo-aortic shunt (CAS) including the LVAD and a cavo-pulmonary connection (CPC). This work aims at realizing a lumped parameter model (LPM) to compare the acute hemodynamic effects of ASD, CPC, CAS, RVAD in LVAD pediatric patients with RVF. Methods: Data of 5 pediatric patients undergoing LVAD were retrospectively collected to reproduce patients baseline hemodynamics with the LPM. The effects of continuous flow LVAD implantation complicated by RVF was simulated and then the effects of ASD, CPC, CAS and RVAD treatments were simulated for each patient. Results: The model successfully reproduced patients' baseline and the hemodynamic effects of the surgical strategies. Simulating the different surgical strategies, an unloading of the right ventricle and an increment of left ventricular preload were observed with an improvement of the hemodynamics (total cardiac output: ASD +15%, CPC +10%, CAS +70% RVAD +20%; right ventricular external work: ASD -19%, CPC -46%, CAS -76%, RVAD -32%; left ventricular external work: ASD +12%, CPC +28%, RVAD +64%). Conclusions: The use of numerical model could offer an additional support for clinical decision-making, also potentially reducing animal experiments, to compare the outcome of different surgical strategies to treat RVF in LVAD.